Dual action ectoparasite vaccine targeting 'exposed' and 'concealed' antigens. - Trimnell, A; Hails, R; Nuttall, P (2002)
Blood-feeding ectoparasites, such as mosquitoes, sandflies and ticks, transmit many disease agents. Their control relies on large-scale, repeated use of chemical pesticides. An alternative, targeted and environmentally friendly approach is to develop anti-ectoparasite vaccines. We describe a vaccine to control ticks that targets an 'exposed' tick saliva antigen and cross-reacts with 'concealed' tick midgut antigens. Ticks feeding on immunised animals induced a cutaneous inflammatory response and increased antibody titer, while engorged ticks died following damage to their midgut. This dual action, acting at the feeding site and in the midgut, offers a self-sustaining strategy for ectoparasite control boosted by natural infestations.